The effect of Avoparcin on the performance of grazing steers - L.R. Corah; W.D. Busby; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1982)
One hundred two steers were used to study the effect of Avoparcin on the performance of grazing steers. Four desired dosages – 0. 200, 400. and 600 mg/head/day – were compared in a self-fed mineral mix. Feeding Avoparcin at the desired level of 400 mg/head/day increased steer gains By 22%.
Keywords: Cattlemen& #x27; s Day; 1982; Report of progress (Kansas State University. Agricultural Experiment Station); 413; Beef; Performance; Steers